2014
DOI: 10.1007/s00044-014-1309-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anti-nociceptive, anti-inflammatory activities of new aroyl propionic acid derivatives including N-acylhydrazone motif

Abstract: In the present study, new 4-[4-[2-(2-(4-substituted benzylidene)hydrazinyl)-2-oxoethoxy]phenyl]-4-oxobutanoic acid derivatives were synthesized, and their antinociceptive and anti-inflammatory activities were investigated. In the synthesis of the compounds, 4-[4-(2-ethoxy-2-oxoethoxy)phenyl]-4-oxobutanoic acid molecule was used as starting material. The intermediate hydrazide compound (1) was reacted with appropriate aromatic aldehydes to obtain final hydrazone compounds (2a-i). All final compounds are well ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…In this study, bicyclic terpenoid (−)-verbenone was used as a base for hydrazone synthesis via its condensation with hydrazides of para-substituted phenoxyacetic acid. As known earlier, phenoxyacetic acid derivatives also possess the peripheral nociceptive action and anticonvulsant effect [12,13]. Taking into account the foregoing, a series of novel (−)-verbenone hydrazones were designed and synthesized, and their spectral characteristics have been described followed by their investigation as potential analgesic and anticonvulsant agents using different experimental models in vivo.…”
Section: Introductionmentioning
confidence: 90%
“…In this study, bicyclic terpenoid (−)-verbenone was used as a base for hydrazone synthesis via its condensation with hydrazides of para-substituted phenoxyacetic acid. As known earlier, phenoxyacetic acid derivatives also possess the peripheral nociceptive action and anticonvulsant effect [12,13]. Taking into account the foregoing, a series of novel (−)-verbenone hydrazones were designed and synthesized, and their spectral characteristics have been described followed by their investigation as potential analgesic and anticonvulsant agents using different experimental models in vivo.…”
Section: Introductionmentioning
confidence: 90%
“…Most of the derivatives were found to exhibit peripheral nociceptive effects. The results demonstrated that the presence of acidic moiety increased the peripheral antinociceptive activity and reduced the central antinociceptive activity [5]. 5) keeping in view that atropine induces central antinociception by increasing cholinergic transmission.…”
Section: Antinociceptive and Antiinflammatory Activitymentioning
confidence: 66%
“…The 2-[(2-substitutedbenzylidene)hydrazinyl]-6-ethoxy-3-nitropyridine derivatives 2a – 2n were synthesized by using a simple previously reported method [ 12 , 13 ] and in accordance with a protocol used in our earlier research. The structures of the synthesized compounds were completely identified by spectral data, as reported in the experimental section.…”
Section: Resultsmentioning
confidence: 99%